Empowering nurses and residents to improve telemetry stewardship in the academic care setting. Issue 5 (19th September 2020) - Duffy, Eamon; Niessen, Timothy; Perrin, Keisha; Apfel, Ariella; Bertram, Amanda; Keller, Sara C.; Feldman, Leonard S.; Pahwa, Amit K.
Abstract: Aims and Objectives: Inappropriate use of telemetry frequently occurs in the inpatient, non‐intensive care unit setting. Telemetry practice standards have attempted to guide appropriate use and limit the overuse of this important resource with limited success. Clinical‐effectiveness studies have thus far not included care settings in which resident‐physicians are the primary caregivers. Methods: We implemented two interventions on general internal medicine units of an academic hospital. The first intervention, or nurse‐discontinuation protocol, allowed nurses to trigger the discontinuation of telemetry once the appropriate duration had passed according to practice standards. The second intervention, or physician‐discontinuation protocol, instituted a best‐practice advisory that notified the resident‐physician via the electronic medical record when the appropriate telemetry duration for each patient had elapsed and suggested termination of telemetry. Data collection spanned 8 months following the implementation of the nurse‐discontinuation protocol and 12 months following the physician‐discontinuation protocol. Results: During the control period, the average time spent on telemetry was 86.29 hours/patient/month. During the nurse‐discontinuation protocol, patients spent, on average, 70.86 hours/patient/month on telemetry. During the physician‐discontinuation protocol, patients spent, on average, 81.6 hours/patient/month on telemetry. During the nurse‐discontinuation protocol, there was no significant change in the likelihood that a patient was placed on telemetry throughout their admission when compared with the control period. During the physician‐discontinuation protocol, there was a significant decrease of 56.1% in the likelihood that a patient would be put on telemetry when compared with the control time period. Conclusions: These findings expand our understanding of telemetry use in the academic care setting in which trainees serve as the primary caregivers. Furthermore, these findings represent an important addition to the telemetry and patient monitoring literature by demonstrating the impact that nurse‐managed protocols can have on telemetry use and by highlighting effective strategies to improve telemetry use by physicians in training.